(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the transformative role of digital technologies in the acquisition and pragmatic application of English vocabulary. In the contemporary pedagogical landscape, the shift from traditional rote memorization to tech-integrated lexical development has redefined communicative competence. This study analyzes the efficacy of various digital tools—ranging from mobile-assisted language learning (MALL) to corpus-based software and Artificial Intelligence (AI)—in fostering lexical depth and breadth. Furthermore, it examines the critical transition from passive word recognition to active, context-aware production in authentic communicative settings. The findings suggest that while technology provides unprecedented access to linguistic data, the "correct application" requires a blended approach that prioritizes socio pragmatic awareness.